Novel Insights into Pyrrolizidine Alkaloid Toxicity and Implications for Risk Assessment: Occurrence, Genotoxicity, Toxicokinetics, Risk Assessment–A Workshop Report - Schrenk, Dieter; Fahrer, Jörg; Allemang, Ashley; Fu, Peter; Lin, Ge; Mahony, Catherine; Mulder, Patrick P.J.; Peijnenburg, Ad; Pfuhler, Stefan; Rietjens, Ivonne M.C.M.; Sachse, Benjamin; Steinhoff, Barbara; These, Anja; Troutman, John; Wiesner, Jacqueline (Planta Medica, 2021)
This paper reports on the major contributions and results of the 2nd International Workshop of Pyrrolizidine Alkaloids held in September 2020 in Kaiserslautern, Germany. Pyrrolizidine alkaloids are among the most relevant plant toxins contaminating food, feed, and medicinal products of plant origin. Hundreds of PA congeners with widespread occurrence are known, and thousands of plants are assumed to contain PAs. Due to certain PAsʼ pronounced liver toxicity and carcinogenicity, their occurrence in food, feed, and phytomedicines has raised serious human health concerns. This is particularly true for herbal teas, certain food supplements, honey, and certain phytomedicinal drugs. Due to the limited availability of animal data, broader use of in vitro data appears warranted to improve the risk assessment of a large number of relevant, 1,2-unsaturated PAs. This is true, for example, for the derivation of both toxicokinetic and toxicodynamic data. These efforts aim to understand better the modes of action, uptake, metabolism, elimination, toxicity, and genotoxicity of PAs to enable a detailed dose-response analysis and ultimately quantify differing toxic potencies between relevant PAs. Accordingly, risk-limiting measures comprising production, marketing, and regulation of food, feed, and medicinal products are discussed.
Keywords: genotoxicity; hepatotoxicity; pyrrolizidine alkaloids; risk assessment; structure-activity relationship; toxicokinetics